HACE1, GLRX5, and ELP2 gene variant cause spastic paraplegies - (:unkn) unknown (SPRINGER HEIDELBERG, 2022)
Hereditary spastic paraplegias (HSPs) are a clinically and genetically heterogeneous group of conditions that are characterized by lower limb spasticity and weakness. Considering the clinical overlap between metabolic causes, genetic diseases, and autosomal recessive HSP, differentiation between these types can be difficult based solely on their clinical characteristics. This study aimed to investigate the genetic etiology of patients with clinically suspected HSP. The study group was composed of seven Turkish families who each had two affected children and three families who each had a single affected child (17 total patients). The 17 probands (14 males, 3 females) underwent whole exome sequencing. Five typical HSP genes (FA2H, AP4M1, AP4E1, CYP7B1, and MAG) and three genes not previously related to HSP (HACE1, GLRX5, ad ELP2) were identified in 14 probands. Eight novel variants were identified in seven families: c.653 T > C (p.Leu218Pro) in the FA2H gene, c.347G > A (p.Gly116Asp) in the GLRX5 gene, c.2581G > C (p.Ala861Pro) in the HACE1 gene, c.1580G > A (p.Arg527Gln) and c.1189-1G > A in the ELP2 gene, c.10C > T (p.Gln4*) and c.1025 + 1G > A in the AP4M1 gene, c.1291delG (p.Gly431Alafs*3) and c.3250delA (p.Ile1084*) in the AP4E1 gene, and c.475 T > G (p.Cys159Gly) in the MAG gene. The growing use of next-generation sequencing improved diagnosis but also led to the continual identification of new causal genes for neurogenetic diseases associated with lower limb spasticity. The increasing number of HSP genes identified thus far highlights the extreme genetic heterogeneity of these disorders and their clinical and functional overlap with other neurological conditions. Our findings suggest that the HACE1, GLRX5, and ELP2 genes are genetic causes of HSP.
Keywords: Spastic paraplegia; Spasticity; HACE1; GLRX5; ELP2; Novel variant